2010
DOI: 10.1007/s10750-010-0334-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress by poor food quality and exposure to humic substances: Daphnia magna responds with oxidative stress, lifespan extension, but reduced offspring numbers

Abstract: In freshwater systems, many abiotic and biotic factors determine the natural fluctuation of Daphnia spec. populations: climatic and water quality parameters, quantitative and qualitative food quality and quantity, predation, and humic substances. Many factors/stressors act in concert. In this contribution, we supplied Daphnia magna with two different diets (chlorococcal alga Pseudokirchneriella subcapitata and baker's yeast) fed ad libitum and exposed it to an environmentally realistic concentration of humic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…[43] Whereas other results indicated that humic substances at low concentrations had the potential to expand the lifespan of D. magna, those same findings also demonstrated that the number of offspring was reduced. [44] Similar negative results were also obtained with the cladoceran Ceriodaphnia dubia [19] or with Latonopsis australis [45] although positive effects of polyphenols were, in fact, reported for specific clones of Moina macrocopa [46,47] and for Daphnia magna at low polyphenol concentrations. [48] Humic substances therefore have been shown to alter the lifespan of the cladocerans.…”
Section: Discussionsupporting
confidence: 54%
“…[43] Whereas other results indicated that humic substances at low concentrations had the potential to expand the lifespan of D. magna, those same findings also demonstrated that the number of offspring was reduced. [44] Similar negative results were also obtained with the cladoceran Ceriodaphnia dubia [19] or with Latonopsis australis [45] although positive effects of polyphenols were, in fact, reported for specific clones of Moina macrocopa [46,47] and for Daphnia magna at low polyphenol concentrations. [48] Humic substances therefore have been shown to alter the lifespan of the cladocerans.…”
Section: Discussionsupporting
confidence: 54%
“…An array of oxidative stress symptoms have been reported in several organisms exposed to HS. These symptoms include reactive oxygen species accumulation and reduced antioxidant capacityeven at very low HS concentrations, membrane lipid peroxidation, and increased activity of antioxidant enzymes (Timofeyev et al 2006a, b;Steinberg et al 2010a). Therefore, Steinberg et al (2003) coined the oxymoron "natural xenobiotics" for HS in relation to their interactions with the biota-in analogy to secondary plant compounds; yet, in contrast to the latter, HS are not synthesized to defend against herbivory, but challenge any exposed organism.…”
Section: Introductionmentioning
confidence: 99%
“…HuminFeedÂź consists of 82% humic substances and 18% low-molecular-weight compounds, and it also contains 43% organic carbon ). It has displayed direct effects on aquatic and sediment organisms including the water mould Saprolegnia parasitica Coker , the water flea Daphnia magna Straus (Euent et al 2008;Bouchnak and Steinberg 2010;Steinberg et al 2010a), Moina macrocopa Straus (Suhett et al 2011), Moina micrura Kurz (Steinberg et al 2010b) and the nematode Caenorhabditis elegans Maupas ).…”
Section: Humic Materialsmentioning
confidence: 99%
“…Dissolved HSs are taken up by some exposed organisms (Wang et al 1999;Steinberg et al 2003) and interact at various biochemical and molecular levels (for reviews, see Steinberg et al 2006Steinberg et al , 2008. Since HSs are natural xenobiotics and aquatic organisms try to get rid of them after their internalization, it is not surprising that HSs induce anti-stress reactions which consume energy and are-at least in part-transcriptionally controlled (Menzel et al 2005;Steinberg et al 2010a). Eventually, this stress can be lethal (Steinberg 2003;Cazenave et al 2006;McMaster and Bond 2008).…”
mentioning
confidence: 99%